ÇOCUK MEDYASI VE DOĞAN KARDEŞ DERGİSİ - Çetin Murat Hazar; Umur Işık (İletişim Kuram ve Araştırma Dergisi, 2017)
CHİLDREN’S MEDIA AND DOGAN KARDES CHILDREN’S MAGAZINE   Abstract The planned study aims to approach Dogan Kardes Children’s Magazine, one of the most important representatives of magazine and children’s media in our country. Magazine content will receive the priority consideration in a contextual manner in this study. Concurrent with the topic, history of magazine and magazine business in our country will be dwelled upon. In the international arena, children’s magazine business has started with the publication named “Leipziger Wochenblatt für Kinder” and “Nidergaschiczhes Wochenblatt für Kinder” in 1722, whereas in our country, it has started with “Mumeyyiz”, going back to the year 1869 and, holding along with being the very first children’s magazine in our country.    Children’s media and role of magazines in children’s media will be considered in this study and Dogan Kardes Children’s Magazine will be investigated as an example. Dogan Kardes Children’s Magazine has an important place among cognate publications as far as its first publication date, activity, employees, and content is concerned. The magazine was first started to be published in 1945 in memorial of Dogan, who was son of Yapi Kredi Bankasi founder Kazım Taskent and who died in 1939 in an avalanche accident. Dogan Kardes Children’s Magazine had an active place in publication arena for 33 years until the year 1988 and it has started to be active again in 2008 within Yapi Kredi Publications. The magazine began to be published with the staff including Vedat Nedim Tor, Sevket Rado, Cemal Nadir, Selma Emiroglu, Sevki Akoren, Neriman Hizir, Nebahat Karaorman, Nahit Tendor, Fahrunnisa Seden and Munevver Alpar, and it occupies an important place both for children and magazine sector. Key Words: Children’s Media, Children’s Magazine,Dogan Kardes Children’s Magazine   Özet Planlanan çalışma ile dergi, çocuk medyası ve ülkemizde bunun önemli temsilcilerinden birisi olan Doğan Kardeş Çocuk dergisinin ele alınması hedeflenmiştir.  Çalışmada öncelikle dergi konusu kavramsal bir biçimde ele alınacaktır. Konuyla koşut olarak çocuk dergiciliğinin 1722 tarihli “Leipziger Wochenblatt für Kinder” ve “Nidergaschiczhes Wochenblatt für Kinder” isimli yayınlarla başlayan uluslar arası tarihi ile ülkemiz açısından kökeni 1869 yılına kadar giden ve ilk çocuk dergisi olma unvanını elinde bulunduran “Mümeyyiz” ile başlayan tarihi üzerinde durulacaktır. Çalışmada daha sonra çocuk medyası ve çocuk medyası içinde derginin rolü tartışılacak ve örnek olay olarak Doğan Kardeş Çocuk Dergisi incelenecektir. Çocuk dergileri arasında Doğan Kardeş Çocuk Dergisi çıktığı süre, etkinliği, çalışanları, içeriği, konusunda benzerleri arasında önemli bir yere sahip olmaktadır. Dergi Yapı Kredi Bankası’nın kurucusu Kazım Taşkent’in 1939 yılında bir heyelan sonucu vefat eden oğlu Doğan’ın anısına 1945 yılından itibaren çıkarılmaya başlanmıştır. Doğan Kardeş Çocuk Dergisi 1978 yılına kadar 33 yıl yayın hayatında aktif yer almıştır. 2008 yılından itibaren ise Yapı Kredi Yayınları bünyesinde tekrar çalışmalarına geri dönmüştür. Vedat Nedim Tör, Şevket Rado, Cemal Nadir, Selma Emiroğlu, Şevki Akören, Neriman Hızır, Nebahat Karaorman, Nahit Tendor, Fahrünnisa Seden, Münevver Alpar gibi bir kadroyla çıkmaya başlayan dergi gerek çocuklar için gerekse dergicilik sektörü için önemli bir yer iştigal etmektedir. Anahtar Sözcükler: Çocuk Medyası, Çocuk Dergisi, Doğan Kardeş Çocuk Dergisi